Space efficient string search algorithms and data structures - Deoghare, Pratik, author; McConnell, Ross, advisor; Bohm, Wim, advisor; Hulpke, Alexander, committee member (Colorado State University. Libraries, 2015)
We address the problem of finding all the occurrences of a pattern of length m in a text of length n. We introduce two new data structures, called the Sloppy Suffix Array and the Super Sloppy Suffix Array. These data structures are space efficient, easy to understand and implement. Sloppy suffix arrays can be built faster than suffix arrays with just one array of n integers; the search algorithms for both have the same time complexity of O(m log n). We also give a space efficient representation for positional de Bruijn graphs using suffix arrays.
Keywords: algorithm; data structure; space efficient; string search